Intracranial Pseudoaneurysms: Evaluation and Management - Zheng, Yongtao; Lu, Zheng; Shen, Jianguo; Xu, Feng (Frontiers in Neurology, 2020)
Intracranial pseudoaneurysms account for about 1% of intracranial aneurysms with a high mortality. The natural history of intracranial pseudoaneurysm is not well understood, and its management remains controversial. This review provides an overview of the etiology, pathophysiology, clinical presentation, imaging, and management of intracranial pseudoaneurysms. Especially, this article emphasizes the factors that should be considered for the most appropriate management strategy based on the risks and benefits of each treatment option.